Myocardial Viability, Functional Status, and Collaterals of Patients With Chronically Occluded Coronary Arteries - Yang, Xueyao; Tian, Jinfan; Zhang, Lijun; Dong, Wei; Mi, Hongzhi; Li, Jianan; Li, Jiahui; Han, Ye; Zuo, Huijuan; An, Jing; He, Yi; Song, Xiantao (Frontiers in Cardiovascular Medicine, 2021)
Objective: Viability and functional assessments are recommended for indication and intervention for chronic coronary total occlusion (CTO). We aimed to evaluate myocardial viability and left ventricular (LV) functional status using cardiovascular magnetic resonance (CMR), and to investigate the relationship between them and collaterals in patients with CTO. Materials and Methods: We enrolled 194 patients with one CTO artery as detected by coronary angiography. Patients were scheduled for CMR within one week after coronary angiography. Results: A total of 128 CTO territories (66%) showed scar based on late gadolinium enhancement (LGE) imaging. There were 1112 segments in CTO territory, while only 198 segments (18%) subtended by the CTO artery showed transmural scar (i.e., > 50% extent on LGE). Patients with viable myocardium had higher LV ejection fraction (LVEF) (56.7%±13.5% vs. 48.3%±15.4%, P<0.001) than those with transmural scar. Angiographically well-developed collaterals were found in 164 patients (85%). There was no significant correlation between collaterals and the presence of myocardial scar (P=0.680) or between collaterals and LVEF (P=0.191). Nevertheless, more segments with transmural scar were observed in patients with poorly-developed collaterals than in those with well-developed collaterals (25% vs. 17%, P=0.010).